การประมาณค่าขนาดสัดส่วนร่างกายเพื่อการออกแบบโต๊ะเก้าอี้นักเรียนระดับประถมศึกษา: Estimation of Body Dimensions for Primary Student Desk and Chair Design - Pochana, Klangduen; Sungkhapong, Angoon (Asian Health, Science and Technology Reports, 2015)
นักเรียนมักจะใช้เวลาในการนั่งในห้องเรียนเป็นเวลานาน แต่จากหลายงานวิจัยพบว่าเฟอร์นิเจอร์ในห้องเรียนมีขนาดที่ไม่สอดคล้องกับขนาดสัดส่วนของนักเรียน ซึ่งในการออกแบบเฟอร์นิเจอร์ในห้องเรียนที่เหมาะสมตามหลักการยศาสตร์จาเป็นที่จะต้องอาศัยขนาดสัดส่วนของนักเรียนที่มีความถูกต้อง อย่างไรก็ตามการวัดขนาดสัดส่วนของนักเรียนต้องอาศัยเวลามากและผู้วัดต้องมีประสบการณ์ ดังนั้นในงานวิจัยนี้จึงมีวัตถุประสงค์ที่จะประมาณค่าของขนาดสัดส่วนร่างกายของเด็กนักเรียน เพื่อการออกแบบโต๊ะเก้าอี้เรียน กลุ่มตัวอย่าง ที่ทาการศึกษาเป็นนักเรียนชั้นประถมศึกษาปีที่ 1-6 จานวน 684 คน โดยเก็บข้อมูลอายุ และวัดสัดส่วนพื้นฐาน 2 สัดส่วนคือ ความสูง (S) และน้าหนัก (W) สัดส่วนสาหรับการออกแบบโต๊ะเก้าอี้ 8 สัดส่วนคือ ความสูงของข้อพับ (PH) ระยะระหว่างสะโพกถึงข้อพับด้านในของหัวเข่า (BPL) ความสูงของข้อศอกขณะนั่ง (EHS) ความกว้างของสะโพกขณะนั่ง (HW) ความหนาของต้นขา (TT) ความสูงของกลางหลัง (SUH) ระยะระหว่างข้อศอกทั้งสองข้าง (EEB) และระยะเหยียดแขนขณะลาตัวตั้งตรง (FR) นาข้อมูลที่ได้มาวิเคราะห์ความสัมพันธ์ของแต่ละตัวแปรโดยใช้ค่าสัมประสิทธิ์สหสัมพันธ์ของเพียร์สันแล้วสร้างสมการถดถอยเชิงเส้นอย่างง่าย และสมการถดถอยเชิงพหุ ซึ่งผลการศึกษาพบว่า ขนาดร่างกายเด็กนักเรียน 7 สัดส่วน ได้แก่ PH, BPL, HW, TT, SUH, EEB และ FR สามารถใช้ข้อมูลพื้นฐาน 3 ตัว คืออายุ ความสูง และน้าหนักในการพยากรณ์ได้เป็นอย่างดี โดยค่า R2 ของสมการถดถอยเชิงเส้นอย่างง่าย และสมการถดถอยเชิงพหุมีค่า 75.4-85.2% และ 76.6%-86.5% ตามลาดับ สาหรับสัดส่วน EHS พบว่า ค่า R2 มีค่าน้อยกว่า 40% จึงไม่แนะนาให้ใช้ตัวแปรพื้นฐานทั้ง 3 ตัวในการพยากรณ์ ผลการศึกษาสรุปว่า สมการที่ได้สามารถนาไปใช้เพื่อประมาณค่าสัดส่วนร่างกายของนักเรียนเพื่อใช้ในการออกแบบขนาดโต๊ะเก้าอี้ที่เหมาะสมและลดความยุ่งยากในการวัดขนาดสัดส่วนของนักเรียนโดยตรงได้ Students spend long hours sitting down in schools. Considering the previously presented results, it was found that there were ergonomic mismatch between students dimension and classroom furniture. To design classroom furniture ergonomically, accurate dimensions of students were essential. However, it was known that measurement of body dimension was time consuming and required skilled measurer. The aim of this study was to develop models for estimation of students' dimensions which were essential for classroom desk and chair design. The sample consisted of 684 students in grade 1-6. Age, statute, and weight of students were collected. Eight anthropometric characteristics required for desk and chair design, were measured, i.e. popliteal height (PH), buttock-popliteal length (BPL), elbow height while sitting (EHS), hip width (HW), thigh thickness (TT), subscapular height (SUH), elbow-to-elbow breadth (EEB), and functional reach (FR). The parameter correlation of collected data were determined by considering Pearson's Correlation Coefficient. Simple linear regression and multiple regression model were developed. It was found that age, statute, and weight were good predictors for estimation of seven students' dimensions which were PH, BPL, HW, TT, SUH, EEB, and FR. The value of R2 for the simple linear regression and multiple regression model were 75.4-85.2% and 76.6%-86.5%, respectively. However, the estimation of EHS was not recommended for using age, statute, and weight as predictors since it showed low R2 value (<40%). The research results showed that the regression models can be used efficiently for estimation of essential students' dimensions, therefore, the complexity of direct measurement of students' dimensions can be abolished.